Reimagining Creativity Development through Inkblot Exploration: Evidence from Loen Sayang Kindergarten - Putri Maqfirah; Mutia Sari; Russy Ranggayoni; Sherif Mohamed A. Ismail; Ayesha Fakhar Naeem (Seulanga : Jurnal Pendidikan Anak, 2026)
The development of children's creativity in Loen Sayang Kindergarten is still underdeveloped as they had limited opportunities to think independently and express ideas through drawing activities. This study aimed to develop the creativity of children aged 5-6 years through inkblot technique activities in Loen Sayang Kindergarten. This study employed a qualitative approach using classroom action research (CAR). The subjects of the study were 15 children in class B1 at Loen Sayang Kindergarten. Data collection techniques include observation, interviews and documentation. Data analysis techniques used are data reduction, data presentation and drawing conclusions. The results of the study in the pre-action 10 children or 66.67% (BB), 5 children or 33.33% (MB), (BSH) and (BSB) has not yet been found. As for the results of the achievement of actions in cycle I, there was an increase, 4 children or 26.67% (BB), 8 children or 53.33% (MB), and 3 children or 20% (BSH) and (BSB) were not yet there. In cycle II, children's creativity increased so that there were no longer any children in the (BB) category. Only 2 children or 13.33% (MB), 6 children or 40% (BSH) and 7 children or 46.67% (BSB). Based on the results of the study, it can be concluded that inkblot technique activities can develop the creativity of children aged 5-6 years.